Tornadoes - Allaby, Michael (New York : Facts On File, 1997)
Provides information about tornadoes, discussing the conditions that lead to their formation, looking at what happens during the course of the ferocious storms, and tracing the wreckage of some of the major twisters of the past.
Includes index.
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Tornadoes; Tornadoes